Factors associated with hepatitis B and C co-Infection among HIV-infected patients in Singapore, 2006 – 2017 - Choy, Chiaw Yee (2020)
Co-infection of hepatitis B virus (HBV) and hepatitis C virus (HCV) with human immunodeficiency virus (HIV) is associated with increased risk of hepatic complications and mortality. A retrospective study to estimate the proportion of HBV and HCV co-infections in Singapore was conducted using a clinical database. We included 3065 patients who were seen under the Clinical HIV Programme at the largest referral centre for HIV care between 2006 and 2017 and were tested for both HBV and HCV. Factors associated with HIV-HBV and HIV-HCV co-infections were determined using logistic regressions. The majority (86.3%) of HIV-infected patients were mono-infected, while 7.2% were co-infected with HBV, 6.0% with HCV, and 0.5% were co-infected with both HBV and HCV. The most common HCV genotype was GT1 (63%). Factors significantly associated with HBV co-infection in the multivariable model were: Aged 30–49 years and 50–69 years at HIV diagnosis, male gender, and HIV transmission through intravenous drug use (IDU). Independent factors associated with HCV co-infection were: Malay ethnicity, HIV transmission through IDU, and HIV diagnosis between 2006 and 2008. Behavioural risk factors such as IDU, as well as epidemiologic differences associated with co-infection, should inform further studies and interventions aimed at reducing viral hepatitis infection among HIV-infected individuals.